PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPOSISI MENGGUNAKAN MODEL PICTURE AND PICTURE PADA SISWA KELAS X SMA NEGERI 1 SUNGAI RAYA KEPUALAUAN - Lutfiya Muhlisah, Suci; Mai Yuliastri Simarmata; Fitri Wulansari; Arni; Fitriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to apply the picture and picture learning model in teaching expository text writing to Class XC students of SMA Negeri 1 Sungai Raya Kepulauan. The research design follows a classroom action research approach. The subjects of the study were 34 students from Class XC at SMA Negeri 1 Sungai Raya Kepulauan. The data collection techniques used in this research include direct observation, direct communication, measurement, and document study. The data collection tools consist of observation sheets, interview sheets, tests, and documentation. The research was conducted in two cycles, namely Cycle I and Cycle II. Each cycle in this study involved four steps: planning, implementation, observation, and reflection. The results of this study show that the learning outcomes for expository text writing using the picture and picture model in Class XC students of SMA Negeri 1 Sungai Raya Kepulauan improved, with the mastery percentage increasing from 29.72% in the pre-cycle stage to 61.76% in Cycle I and 79.41% in Cycle II. It can be concluded that the use of the picture and picture learning model can enhance the learning outcomes for expository text writing among Class XC students of SMA Negeri 1 Sungai Raya Kepulauan.